2015
DOI: 10.1542/peds.2015-0305
|View full text |Cite
|
Sign up to set email alerts
|

Parental Monitoring and Its Associations With Adolescent Sexual Risk Behavior: A Meta-analysis

Abstract: CONTEXT Increasingly, health care providers are using approaches targeting parents in an effort to improve adolescent sexual and reproductive health. Research is needed to elucidate areas in which providers can target adolescents and parents effectively. Parental monitoring offers one such opportunity, given consistent protective associations with adolescent sexual risk behavior. However, less is known about which components of monitoring are most effective and most suitable for provider-initiated family-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 62 publications
4
91
1
8
Order By: Relevance
“…55, 56 Yet many parents do not communicate with adolescents because of embarrassment, lack of confidence, and uncertainty about what to say. 57 Implementing a brief and effective intervention such as the FTT model is a way to improve parent–child communication and effectively monitor adolescent behavior, leading to delayed sexual debut and reduced frequency of sex.…”
Section: Calls For Improvementmentioning
confidence: 99%
“…55, 56 Yet many parents do not communicate with adolescents because of embarrassment, lack of confidence, and uncertainty about what to say. 57 Implementing a brief and effective intervention such as the FTT model is a way to improve parent–child communication and effectively monitor adolescent behavior, leading to delayed sexual debut and reduced frequency of sex.…”
Section: Calls For Improvementmentioning
confidence: 99%
“…Research has shown that positive family processes, like parental monitoring and family social support, decrease risk-taking among adolescents (3), whereas negative family processes, like family conflict, often have the opposite effect (16). Parental monitoring is consistently linked with lower levels of risk behaviors, including substance use and sexual risk behaviors, and protects against early initiation (1722). Although the beneficial effects of parental monitoring are well established (3), there may be gender differences in the impact of parental monitoring on risk-taking among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Moderation analyses revealed larger effects for girls (r = .12) than boys (r = .04), which raises questions about the effectiveness of parent-child communication about sex for promoting boys’ sexual health. The second meta-analysis included 30 studies of over 40,000 adolescents and found that higher parental knowledge about the adolescent’s activities and whereabouts was associated with increased condom use, but parental monitoring, or tracking and enforcing rules for adolescent behaviors (e.g., homework, using drugs or alcohol), was not 27 . There was significant heterogeneity in effect sizes across studies, suggesting further research is needed that can help build a literature where effect moderators can be identified.…”
mentioning
confidence: 99%